The Impact of Key Audit Matter Disclosures on Audit Report Lag in Indonesia - Azkia, Syarifah Nailul; Rosdini, Dini; Sukmadilaga, Citra (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Timely audited financial reporting is essential for maintaining the relevance of accounting information and reducing information asymmetry among stakeholders. Following the implementation of SA 701, Key Audit Matter (KAM) disclosures have become an important component of auditor reporting that may influence audit completion time. This study examines whether KAM disclosure characteristics affect Audit Report Lag (ARL) among non-financial firms listed on the Indonesia Stock Exchange during 2022–2024.This study employs panel data regression using 771 firm-year observations from 257 firms in the consumer cyclicals, property and real estate, and energy sectors. The results show that the number of KAMs has no significant effect on ARL. By contrast, the length of KAM disclosure is negatively affect ARL. In addition, firm size, profitability, leverage, and audit opinion do not significantly affect ARL. These findings imply that the length of KAM disclosure, rather than its quantity, is more relevant in explaining audit timeliness in Indonesia.